Raman study of lower toxicity polymer gel for radiotherapy dosimetry - Adenan, Mohd Zulfadli; Ahmad @ Ayob, Mansor; Mohd Noor, Noramaliza; Deyhimihaghighi, N.; Saion, Elias (IOP Publishing, 2014)
N-isopropyl acrylamide (NIPAM) monomer and N, N' – methylene-bis-acrylamide (BIS) crosslinker were used to synthesize polymer gel dosimeters for a reason that the monomer is lower toxicity which gives a significant advantage over the other polymer gel compositions. The gels were irradiated with Co-60 gamma rays at doses up to 21 Gy and the irradiated NIPAM polymer gels were used to investigate the dose response characteristics based on Raman spectroscopy analysis on the formation of the polymer gels and the consumptions of NIPAM and BIS co-monomers. From the findings, the polymerization was referred to an increment in Raman intensity at 815 cm−1, assigned for C-C stretching mode of NIPAM polymer gel, as the dose increased. The consumptions of the co-monomers were referred to a decrement in Raman intensities at 1025 cm−1 2353 cm−1 for C=C stretching modes of NIPAM and BIS respectively as the dose increased. The increment and decrement in Raman intensities of polymer and co-monomers respectively with increase of dose indicate that there is occurrence of polymerization of NIPAM polymer gels which could be applied in 3D dose distributions for radiotherapy treatment planning. The correlation factor kBIS is greater than kNIPAM showing that the reaction of BIS crosslinker is more efficient than NIPAM monomer to generate 37% of the NIPAM polymer gel.